Correlation of apoptotic related protiens and clinicopathological parameters in liposarcoma - Abd Alabbas, Haider K. (2012)
Information on prognostic factors is important to setup a proper therapeutic modalities for soft tissue sarcomas. Tumor growth depends on two distinctive pathways: cell proliferation and apoptosis. Liposarcoma is one of the most common soft tissue sarcomas (account about 20-30%), thus this study was designed to look into apoptotic activity of LPS as single entity. In relation to that, we also try to correlate the relationship between apoptotic activity and the clinic-pathological parameters. A cross sectional study was conducted from April 2009 To October 2011. 45 cases of different histologic subtypes of LPS were included in this study. Tissue sections that were retrieved from archived tissue blocks were stained with immunohistochemical stain for Bcl-2 and Bax proteins. Higher expression of Bax in the tumor cells (71.1%) was seen compared to the expression of Bcl-2 (48.9%). Significant correlation between the expression of Bcl-2 and tumor grade (p< 0.005) and histologic subtypes (p<0.001) were found. At the same time Bax expression is higher in LPS and significantly correlate with histological grade and the site of the tumors (p<0.048) and histologic grade (p<0.014). However, there were no correlation between apoptotic activity and tumor size, tumor depth and surgical margins. In conclusion, apoptotic activity plays an important role in tumor developments and progression. Immunohistochemical detection of the proteins used in this study might be useful as markers for predicting the prognosis in LPS.